2003
DOI: 10.1289/ehp.5800
|View full text |Cite
|
Sign up to set email alerts
|

An approach to assessment of endocrine disruption in the National Children's Study.

Abstract: In this article we consider the importance of assessing endocrine disruption in a large new cohort that has been proposed, the National Children's Study (NCS). We briefly review evidence that endocrine disruption is a potentially important hypothesis for human studies and weigh the need to assess endocrine disruption in the NCS. We note the salient features of earlier, similar cohort studies that serve as reference points for the design of the NCS. Finally, we discuss features of the NCS that would allow or en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…G-based herbicides are known to disrupt endocrine functions and have been extensively investigated for their effect on reproduction by both in vivoand in vitro experiments (Stamati et al, 2007;Hamdaoui et al, 2018). However, only a few studies have investigated the toxic effect of G-based herbicides on the thyroid gland.To our knowledge, this study may constitute the first attempt to evaluate the toxic effect on thyroid gland in female rats although several studies have demonstrated the significant relationship between circulating levels of thyroid hormones and exposure to other environmental chemicals (Longnecker et al, 2003;Blount et al, 2007).Our results showed that KL sub-chroic exposure Fig.2 (B, C and C1).Our histological finding is in favor of hypothyroidism of treated rats. It is a condition where in the thyroid gland is not capable of producing enough thyroid hormone.…”
Section: Discussionmentioning
confidence: 46%
“…G-based herbicides are known to disrupt endocrine functions and have been extensively investigated for their effect on reproduction by both in vivoand in vitro experiments (Stamati et al, 2007;Hamdaoui et al, 2018). However, only a few studies have investigated the toxic effect of G-based herbicides on the thyroid gland.To our knowledge, this study may constitute the first attempt to evaluate the toxic effect on thyroid gland in female rats although several studies have demonstrated the significant relationship between circulating levels of thyroid hormones and exposure to other environmental chemicals (Longnecker et al, 2003;Blount et al, 2007).Our results showed that KL sub-chroic exposure Fig.2 (B, C and C1).Our histological finding is in favor of hypothyroidism of treated rats. It is a condition where in the thyroid gland is not capable of producing enough thyroid hormone.…”
Section: Discussionmentioning
confidence: 46%
“…Various cannabinoids have been shown to interact with the endocrine system and have been noted to act as endocrine disruptors in ovaries, testes and placenta [ 126–130 ], and cannabinoids are also involved in breast pathophysiology [ 11 , 131 ] and are normally excreted in breast milk [ 132 , 133 ]. Endocrine disruption has been noted to be a powerful negative impactor of human health [ 134 , 135 ]. Agonists at the Type 1 and 2 cannabinoid receptors (CB1R and CB2R) are known to interfere with the hypothalamic-pituitary-gonadal axis in human females [ 11 ], hypothalamic-pituitary-adrenal axis [ 136–138 ], with insulin [ 139 , 140 ] and other hormones and to stimulate human prolactin levels [ 141–143 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various analysis options are described in the literature, relating to the types of variables that work well in certain types of statistical approaches (continuous, dichotomous and categorical variable types) and statistical testing that allows for the use of large datasets over time ( Eldred and Darrah, 2010 , Longnecker et al, 2003 , Wigle et al, 2008 ).…”
Section: Methodological Considerations In the Collection Of Data And mentioning
confidence: 99%